Answer:
The following expressions become negative:
- 3) x times y = xy = (1)(-2) = -2
- 4) x divided by y = x/y = 1/-2 = -2
Explanation:
Given
Computing by substituting x = 1, and y = -2
1) x+y = 1+(-2) = -1
2) x - y = 1 - (-2) = 1+2 = 3
3) x times y = xy = (1)(-2) = -2
4) x divided by y = x/y = 1/-2 = -2
It is clear from the above calculations that when we put x = 1, and y=-2 then the expressions (x+y), (x times y), and (x divided by y) become negative.
Therefore, the following expressions become negative:
- 3) x times y = xy = (1)(-2) = -2
- 4) x divided by y = x/y = 1/-2 = -2